2014
DOI: 10.1161/atvbaha.114.303966
|View full text |Cite|
|
Sign up to set email alerts
|

Phospholipid Transfer Protein Destabilizes Mouse Atherosclerotic Plaque

Abstract: 16Apoptotic macrophages, especially in advanced plaques, promote several processes that contribute to plaque instability. 17 PLTP could augment apoptosis in THP-1 (human acute monocytic leukemia cell line) cell-derived macrophages 18 and PLTP stimulates Janus family kinase 2 phosphorylation, 19 involved in apoptosis in several cells, including macrophages. 20 Therefore, PLTP-related plaque instability may be mediated by macrophage apoptosis.In this study, we evaluated the association of PLTP and atheroscleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In mouse models, it has been demonstrated that global PLTP deficiency reduces atherosclerotic lesion size (63) and the plaque stability (105), while its overexpression shows the opposite effect (106). Global PLTP deficiency in mice is also associated with abdominal aortic aneurysm (80).…”
Section: Pltp and Atherosclerosismentioning
confidence: 99%
“…In mouse models, it has been demonstrated that global PLTP deficiency reduces atherosclerotic lesion size (63) and the plaque stability (105), while its overexpression shows the opposite effect (106). Global PLTP deficiency in mice is also associated with abdominal aortic aneurysm (80).…”
Section: Pltp and Atherosclerosismentioning
confidence: 99%
“…The result supports the observation of the importance of passive HDL transport ( Kareinen et al, 2015 ). Adenoviral overexpression of PLTP in hepatocytes generates larger particle size (<7.1 nm but larger than lipid-free ApoA1; Ji et al, 2014 ) and also increases atherosclerotic lesion size in PLTP overexpressing ApoE deficient mice ( Zhang et al, 2014 ), although the causal relationship between PLTP and CVD is still under debate ( Vergeer et al, 2010 ; Kim et al, 2015 ). In line with the mechanism proposed by Zhang et al (2014) , the increased HDL particle size resulting from PLTP overexpression impaired RCT ( Samyn et al, 2009 ), perhaps impairing movement of HDL into the interstitium, limiting cholesterol uptake from extravascular spaces like plaque, and ultimately increasing atherosclerotic disease progression.…”
Section: Hdl Transport From Plasma To Lymphmentioning
confidence: 99%
“…Finally, mice deficient in phospholipid transfer protein (PLTP), a protein known to correlate with atherosclerosis severity, showed reduced levels of RIPK3 in atherosclerotic plaques in addition to reduced atherosclerotic lesion burden and intra-lesion cell death. Overexpression with a PLTP-containing adenovirus vector conversely increased RIPK3 protein levels detected in murine atherosclerotic plaques, lesion area and intra-lesion cell death [23]. These findings collectively suggest that necroptosis occurs in human atherosclerotic disease and that RIPK1 and RIPK3 contribute to the atherosclerosis pathophysiology.…”
Section: Ripk1 and Ripk3 In Atherosclerosismentioning
confidence: 63%